A STORY OF RANG KAYO HITAM IN ANIMATION FILM BY AKHMAD FAWWAZ POLITICAL ECOLOGY APPROACH - Febrianti, Maya (Universitas Andalas, 2019)
Rang Kayo Hitam story is a story that developed in Jambi Province, stories originating from folklore began to be published through the YouTube application, in broad outline this animated film has represented oral stories and written stories. This paper discusses the study of political ecology in the story of Rang Kayo Hitam in animated films. The purpose of this study is to describe the political ecology of the Rang Kayo Hitam story in an animated film. The data source is the animated film Rang Kayo Hitam. Qualitative description research method. Research analysis by listening to dialogue in animated films repeatedly, grouping texts that are included in political ecology. The results of this study are the story of Rang Kayo Hitam in this animated film that still contains political ecology involving the Malay kingdom of Jambi and the kingdom of Mataram, the two kingdoms which have their own policies on their territory.